Nano-Metal–Organic Framework Decorated With Pt Nanoparticles as an Efficient Theranostic Nanoprobe for CT/MRI/PAI Imaging-Guided Radio-Photothermal Synergistic Cancer Therapy - Ma, Yingjian; Mao, Jing; Qin, Haojie; Liang, Pan; Huang, Wenpeng; Liu, Chenchen; Gao, Jianbo (Frontiers in Bioengineering and Biotechnology, 2022)
Nowadays, the multifunctional theranostic nanoplatforms, which can realize changing the contrasts of medical images and enhance cancer therapies simultaneously, have attracted tremendous attention from chemists and medicine in past decades. Herein, a nanoscale metal-organic framework-based material was firstly synthesized and then decorated with platinum (NMOF545@Pt) successfully for multimodal imaging‐guided synergistic cancer therapy. The obtained NMOF545@Pt is advantageous in shortening the longitudinal relaxation time (T1), enhancing photoacoustic effects, and elevating X-ray absorption efficiently. Thus, the enchantments of tripe imaging modalities computed tomography (CT) /magnetic resonance imaging (MRI) /photoacoustic imaging (PAI) were realized with NMOF545@Pt administration simultaneously and can be cleared from the mice. Meanwhile, the in vitro and in vivo experiments demonstrate that the synthesized NMOF545@Pt can dramatically increase photothermal therapy (PTT) and radiotherapy (RT) efficacy. Convincing evidence proves that tumor growth can be wholly inhibited without any noticeable side effects or organ damage. The results demonstrated the promise of multifunctional nanocomposites NMOF545@Pt to improve biomedical imaging and synergistic tumor treatments.